2019
DOI: 10.1098/rsos.182195
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cd(II) in water by mesoporous ceramic functional nanomaterials

Abstract: Mesoporous ceramic functional nanomaterials (MCFN) is a self-assembled environmental adsorbent with a monolayer molecular which is widely used in the treatment of industrial wastewater and contaminated soil. This work aimed to study the relationship between the adsorption behaviour of Cd(II) by MCFN and contact time, initial concentration, MCFN dosage, pH, oscillation rate and temperature through a batch adsorption method. The adsorption kinetic and isotherm behaviours were well described by the pseudo-second-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…As mentioned by Hossein et al, on increasing pH from 4 to 7, the percent of photoreduction decreased . It is suggested that the photoreduction of the metallic cation is significantly dependent on their tendency toward the hydrolysis reaction. ,, …”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…As mentioned by Hossein et al, on increasing pH from 4 to 7, the percent of photoreduction decreased . It is suggested that the photoreduction of the metallic cation is significantly dependent on their tendency toward the hydrolysis reaction. ,, …”
Section: Methodsmentioning
confidence: 84%
“…Heavy metals such as lead, mercury, cadmium, nickel, and chromium are found in the wastewater of various industries such as mining, petrochemicals, pharmaceuticals, plastic products, paper, and fabric dyeing. Because of the adverse effects of heavy metals, many of their derivatives are classified as pollutants . Penetration of heavy metals inside the body leads to various adverse effects and also many diseases .…”
Section: Introductionmentioning
confidence: 99%
“…The effects on Cd sorption of five operational conditions were studied: wastewater pH, adsorbent dosage, contact time, metal concentration and wastewater salinity. The experimental conditions for Cd adsorption were adapted from suitable references [31][32][33][34][35]. The setup for Cd sorption with the ranges of the operational conditions is presented in Figure 2.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…PEO is a crystalline thermoplastic water-soluble polymer with the molecular formula of H-(-O-CH 2 -CH 2 -)n-OH. Changes in PEO molecular weight determine its properties [21]. In addition to SA, nanomaterials have been also suggested to be promising to remove environmental heavy metals due to their silica and phosphorus-containing minerals, recyclability, and specific surface area as large as 180 m 2 •g −1 .…”
Section: Introductionmentioning
confidence: 99%